The Effects of Prechilling, Chemical and Physical Scarification and Preheating Shock on Seed Gerimination in Capparis spinosa - Solmaz NAJAFI; Sebahattin ÖZCAN; Mehdi TAJBAKHSH (ISPEC Journal of Agricultural Sciences)
This study evaluated various seed treatments to identify optimal methods for enhancing the germination of Capparis spinosa (C. spinosa) seeds. Four treatments were tested: (1) sulfuric acid (98%) for 1 hour followed by 250 ppm gibberellic acid (GA3) for 1 hour; (2) soaking in water for 4 hours followed by chilling at 4°C for 24 hours; (3) soaking in water for 4 hours, chilling at -10°C for 7 days, and GA3 treatment for 1 hour; (4) soaking in hydrochloric acid (37%) for 6 hours followed by GA3 treatment for 1 hour. A completely randomized design with three replicates was used. Analysis of variance (ANOVA) revealed significant differences in germination percentage, mean germination time (MGT) at the 0.05 level, and germination rate index (GRI) at the 0.01 level. Treatments 1, 3, and 4 resulted in the highest germination percentages of 73%, 71%, and 73%, respectively, while Treatment 2 had the lowest at 51%. For MGT, Treatments 1, 2, and 3 ranked highest with values of 7.53, 7.38, and 7.21 days, respectively, whereas Treatment 4 ranked lowest at 8.4 days. The highest GRI values were observed in Treatments 1 and 3, with values of 4.89 and 5.14, respectively, and the lowest in Treatment 2 at 3.64. Results suggest that combining sulfuric acid scarification or chilling at -10 °C with GA3 significantly enhances germination. These findings provide practical insights for improving the germination of Capparis seeds, beneficial for large-scale cultivation and conservation efforts.